(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
Efficient management of patient data and timely clinical decision-making are critical challenges in modern healthcare systems. The increasing volume of medical information requires the use of structured information systems capable of organizing data and supporting healthcare professionals in clinical practice. Medical informatics provides effective tools for integrating patient data management with decision support functionalities.